Character Education Strategy at Boarding School - Mahmud Mahmud; Muhammad Hanif; Muhammad Fahmi Hidayatullah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The purpose of this article is to describe and determine the planning, implementation, and evaluation of character education at the Qur'an Al-Qosimi Islamic Boarding School. The method in this study uses a qualitative method with the type of case study. The subjects of this study were students of the Al-Qur'an Al-Qosimi Islamic Boarding School. From the findings obtained from character education in PPQ through habituation, giving advice, exemplary, practice and giving rewards and punishments. This article produces (1) Planning that adapts the vision and mission from here, each supervisor has various strategies according to their creativity and abilities. (2) Implementation, namely training and instilling the spirit of honesty, independence, responsibility, compassion, mutual cooperation, simplicity, this can be realized by practicing habituation in everyday life, monitored, supervised, sanctioned, and rewarded, students will be stimulated to do which is even better every time you take action. (3) Evaluation of character formation cannot be carried out by administrators and caregivers alone but must involve other parties as supporters of the success of character education at PPQ so that PPQ cooperates with the pesantren community, santri guardians, and monitors every activity inside and outside the pesantren, so that makes it easier to evaluate each individual student.